Citizenship survey, 2005-2011: Secure Access (Citizenship survey, 2021)
The Citizenship Survey (known in the field as the Communities Study) ran from 2001 to 2010-2011. It began as the 'Home Office Citizenship Survey' (HOCS) before the responsibility moved to the new Communities and Local Government department (DCLG) in May 2006. The survey provided an evidence base for the work of DCLG, principally on the issues of community cohesion, civic engagement, race and faith, and volunteering. The survey was used extensively for developing policy and for performance measurement. It was also used more widely, by other government departments and external stakeholders to help inform their work around the issues covered in the survey. The survey was conducted on a biennial basis in 2001, 2003, 2005 and 2007-2008. It moved to a continuous design in 2007 which means that data became available on a quarterly basis from April 2007. Quarter one data were collected between April and June; quarter two between July and September; quarter three between October and December and quarter four between January and March. Once collection for the four quarters was completed, a full aggregated dataset was made available, and the larger sample size allowed more detailed analysis.